Pengendalian Alternatif Hama Serangga Sayuran dengan Menggunakan Warna sebagai Perangkap Mekanis - Lukmanul Hakim; Erdi Surya; Abdul Muis (Universitas Serambi Mekkah, 2017)
This study aimed to test a two models of trap insects, which are made from paper media trap color and light color. The color of tested is red, yellow, and green, while the colored light consisting of light red, yellow, and green. This study was conducted from July to August 2016. This study was conducted at the experimental garden